2000
DOI: 10.1021/ma991695v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Dendritic Poly(ether imide)s

Abstract: New dendritic poly(ether imide)s were synthesized by the convergent growth approach, using 1-(4-aminophenyl)-1,1-bis(4-hydroxyphenyl)ethane, as the building block. The aromatic nucleophilic substitution of the building block with 3-nitro-N-phenylphthalimide led to the first-generation dendron with aminophenyl group at the focal point, which was subsequently reacted with 3-nitrophthalic anhydride to yield the dendritic wedge containing an activated nitro group. The resulting nitro functionality was allowed to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Generally, bisphenols29–33 and diamines33–36 could be prepared by acid‐catalyzed condensation of ketone or aldehyde compounds with excess phenol or aniline. Ketone/aldehyde compounds with35, 36 or without29, 32–34 the electron‐donating phenolic‐OH or amino groups can carry out the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, bisphenols29–33 and diamines33–36 could be prepared by acid‐catalyzed condensation of ketone or aldehyde compounds with excess phenol or aniline. Ketone/aldehyde compounds with35, 36 or without29, 32–34 the electron‐donating phenolic‐OH or amino groups can carry out the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…These results seem conflict with our speculation, but actually they are not. Supporting Information Scheme S1 shows the possible mechanism of stabilization of carbocation in the work of Shu and coworkers30 and Li et al31 As in Supporting Information Scheme S1, after one phenol reacted with the carbonyl group of 4‐nitroacetophenone, the resulting carbocation was stabilized by the phenolic‐OH. Since the resonance between the phenolic‐OH and the carbocation stabilized the carbocation, the electrophilic substitution of second phenol on the carbocation proceeds.…”
Section: Resultsmentioning
confidence: 99%
“…There are a few publications on dendritic aromatic polyimides prepared by stepwise reactions. Shu and coworkers35, 36 reported the preparation of dendritic poly(ether imide)s by a convergent growth approach, using 1‐(4‐aminophenyl)‐1,1‐bis(4‐hydroxyphenyl)ethane as a building block (Scheme ). The aromatic nucleophilic substitution of the building block with 3‐nitro‐ N ‐phenylphthalimide led to the first‐generation dendron ( 18 ) with an aminophenyl group at the focal point.…”
Section: Preparation Of Dendritic and Hyperbranched Polyimidesmentioning
confidence: 99%
“…Dendritic poly(ether imide)s can be prepared from 2B and 3-nitro-N-phenylphthalimide having high reactivity at room temperature. 28 Preliminary experiments, however, suggested that hyperbranched poly(ether imide)s cannot be obtained under the same condition from corresponding monomers, 3A-D, due to low reactivity. Poly(ether imide)s, 4A-D, were prepared by selfcondensation of corresponding monomers, 3A-D, at high temperature and in the presence of potassium carbonate, as shown in Scheme 2.…”
Section: Synthesis and Properties Of Hyperbranched Poly(ether Imide)s...mentioning
confidence: 99%
“…25,26 Recently, Kakimoto's group 27 prepared new aromatic hyperbranched polyimides from 1,4-phenylenediamine (A 2 ) and tri(phthalic acid methyl ester) (B 3 ) in the presence of condensation agent. Shu et al [28][29][30] reported the synthesis of dendritic poly(ether imide)s from the building block 1-(4-aminophenyl)-1,1-bis(4-hydroxyphenyl)ethane and hyperbranched poly(ether imide)s from AB 2 monomer containing a fluoro-substituted phthalimide. In this paper, we report synthesis and characterization of various aromatic hyperbranched poly(ether imide)s with hydroxy, cyanophenyl, aromatic imide, aryl ester, and alkyl ester end groups from AB 2 monomers containing a chloro-substituted phthalimide.…”
Section: Introductionmentioning
confidence: 99%